Urban Cooling Potential: System Losses from Microclimates. (November 2015) - Meggers, Forrest; Aschwanden, Gideon; Teitelbaum, Eric; Guo, Hongshan; Bruelisauer, Marcel
Abstract: Temperatures in the cities are amplified through the urban heat island effect by an additional 2-4 ̊C. The trapping of solar energy in urban canyons and infrastructural plays the most significant role. But use of air conditioning for cooing during summer months is very prevalent in large cities such as New York, and it converts even more energy (electricity) into heat that is rejected into the external environment. The temperature of the environment actually directly controls the efficiency of the common refrigeration cycle found in air conditioning systems by the second law of thermodynamics. A city, with its complex topography of urban canyons and skyscrapers, produces small microclimates with varying temperatures. This project investigates three urban settings that create microclimates that are detrimental for the efficiency of cooling in New York. First, the overall urban heat island effect, second the effect of roof temperature on rooftop package air conditioning units, and third, the impact of local heat emission from agglomerations of window air conditioners. The efficiency loss is investigated by considering the range of temperature changes that can be observed in the surrounding environment of air conditioning system, and determining the subsequent impact on the Coefficient of Performance (COP). Our COP analyses indicate a range of potential energy increases of around 10% to 70% due to increases in environmental temperature around air conditioners. An analysis of the building stock of New York City showed that the electrical energy demand is potentially increased by these effects by 500 TJ from UHI, 75 TJ from rooftop package units, and 370 TJ from window units.